Presidents, Battles, and Must-See Civil War Destinations : a My Old Kentucky Road Trip. - M. Ludwick, Cameron (Indiana University Press, 2019)
Featuring step-by-step guidelines and exclusive tips on sites, monuments, and attractions from presidential homes to the best modern re-enactments, Presidents, Battles, and Must-See Civil War Destinations helps the whole family experience and enjoy history together.